Vesicular stomatitis virus enters cells through vesicles incompletely coated with clathrin that depend upon actin for internalization. - David K Cureton; Ramiro H Massol; Saveez Saffarian; Tomas L Kirchhausen; Sean P J Whelan (PLoS Pathogens)
Many viruses that enter cells by clathrin-dependent endocytosis are significantly larger than the dimensions of a typical clathrin-coated vesicle. The mechanisms by which viruses co-opt the clathrin machinery for efficient internalization remain uncertain. Here we examined how clathrin-coated vesicles accommodate vesicular stomatitis virus (VSV) during its entry into cells. Using high-resolution imaging of the internalization of single viral particles into cells expressing fluorescent clathrin and adaptor molecules, we show that VSV enters cells through partially clathrin-coated vesicles. We found that on average, virus-containing vesicles contain more clathrin and clathrin adaptor molecules than conventional vesicles, but this increase is insufficient to permit full coating of the vesicle. We further show that virus-containing vesicles depend upon the actin machinery for their internalization. Specifically, we found that components of the actin machinery are recruited to virus-containing vesicles, and chemical inhibition of actin polymerization trapped viral particles in vesicles at the plasma membrane. By analysis of multiple independent virus internalization events, we show that VSV induces the nucleation of clathrin for its uptake, rather than depending upon random capture by formation of a clathrin-coated pit. This work provides new mechanistic insights into the process of virus internalization as well as uptake of unconventional cargo by the clathrin-dependent endocytic machinery.